Removal and Preconcentration of Calcium from Industrial Water by Synthesis of Ionic Imprinted Polymer - Mohsen, Hassan N.; Al-Bayati, Yehya K. (Journal of Petroleum Research and Studies, 2025)
Removal and preconcentration of Calcium from industrial water By employing several monomers, including Styrene and 1-vinyl imidazole, bulk polymerization was used to create unique Calcium (II) ion-imprinted polymers (IIPs). To achieve the highest adsorption capacity, the molar ratios of the template, monomer, cross-linking agent, solvents, and different monomers for polymerization were studied. scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and Fourier-transform infrared spectroscopy (FTIR) were used to characterize the produced calcium-IIPs. The maximum capacity for calcium-IIP adsorption was 222.1 mol/g for calcium-IIP2 and 272.6 mol/g for calcium-IIP1 (both of which used styrene as a monomer). Calcium-IIP adsorption complied with Langmuir isotherm models. Before and after treatment, samples of industrial water are obtained from refineries to eliminate chemical components from the water. These solutions were filtered via a 0.5 m filter before being added to the Calcium-IIP-SPE packed column system. to eliminate calcium ions and measure them.